Wholesale price versus buyback: A comparison of contracts in a supply chain with a behavioral retailer. (December 2021) - Vipin, B.; Amit, R.K.
Highlights: Wholesale price contract can coordinate a behavioral supply chain in certain settings. We derive conditions under which buyback contract will not coordinate a supply chain. Our study investigates the structural properties of wholesale price contract. We validate our model with the experimental?ndings from the literature. Abstract: Traditional modeling in supply chain contract analysis shows that a wholesale price contract cannot coordinate a supply chain, whereas a buyback contract can coordinate. In this study, we consider a supply chain involving a risk-neutral supplier and a behavioral retailer under wholesale price and buyback contracts. We characterize the structural properties of the wholesale price contract in a supply chain with a behavioral retailer. Our study reveals that a wholesale price contract can coordinate a supply chain with a behavioral retailer under certain conditions. Under the same conditions, our analysis shows that a buyback contract coordinates the supply chain. Furthermore, we derive the conditions under which a buyback contract will not coordinate a supply chain involving a behavioral retailer. We validate our model with the existing experimental results on supply chain contracts. Finally, we show that a wholesale price contract can outperform a buyback contract in a supply chain having a behavioral retailer.